PENGARUH KINERJA KEUANGAN PERUSAHAAN TERBUKA TERHADAP RETURN SAHAM PADA MASA PANDEMI COVID-19 (Pada Perusahaan yang Tercatat di BEI Tahun 2020) - Alphasyah Lazuardy Sidarta; Ade Irma Suryani Lating; Syarifudin Syarifudin (Media Mahardhika, 2021)
This study aims to determine whether the ongoing global pandemic affects the company's financial performance. This is evidenced by testing the effect of Return On Assets, Debt to Equity Ratio, and Current Ratio on stock returns of companies listed on the Indonesia Stock Exchange in 2020. This study uses a quantitative approach method with multiple linear regression analysis method in partial (Test t) and in simultaneous (Test F) research variables. The sample is taken using a purposive sampling method, so that 35 data are obtained in the form of company financial report which is acquired from the official website www.idx.co.id. The secondary data analysis process in this study is assisted by using the STATA MP14 assistance program. The result shows that all the independent variables used, including the current ratio, debt to equity ratio, and return on assets have an effect on the dependent variable, that is stock returns. By the presence of this result on the study, it is hoped that the company's management can pay attention to various factors that can attract investors to invest in the company, so it will be able to provide optimal returns for investors and for investors will be able to choose and identify a company by analyzing its financial reports that have been published and also by analyzing external factors that can affect the company's performance before investing, in order to get optimal returns in the future